ECD STAKEHOLDERS’ CONCEPTUALISATION OF QUALITY CHILD CARE: A CASE STUDY OF TWO SELECTED PRIVATE DAY CARE SETTINGS IN ZIMBABWE - Dube, Lekani; Dzviti, Vesta (IJRDO - Journal of Business Management, 2016)
This article explored ECD stakeholders’ conceptualisation of quality child care at two privately owned day care settings in one selected district in Zimbabwe. The case study design embedded in the qualitative paradigm was employed in the research. The two day care centres were purposively selected because they enrol toddlers. Study participants were made up of two day care proprietors, four centre caregivers and 20 parents of children enrolled at the centres. The observation, questionnaire and interview were used as data collection methods. Major findings of the study were: ECD stakeholders’ conceptualisation of quality child care was rather narrow, and this resultantly negatively impacted on the quality of childcare at day care settings. The researchers concluded that childcare in day care settings falls far short of the expectations of ECD experts. The study therefore, recommended that responsible authorities conscientise day care proprietors, centre caregivers and parents on quality childcare indicators so that they develop an informed understanding which should improve their day care service delivery. The researchers also recommend that responsible authorities implement and enforce state ECD licensing regulations as way of ensuring that day care environments promote child growth and development to their fullest potential.